2014
DOI: 10.1002/2014jb011180
|View full text |Cite
|
Sign up to set email alerts
|

Cooling magma model for deep volcanic long‐period earthquakes

Abstract: Deep long-period events (DLP events) or deep low-frequency earthquakes (deep LFEs) are deep earthquakes that radiate low-frequency seismic waves. While tectonic deep LFEs on plate boundaries are thought to be slip events, there have only been a limited number of studies on the physical mechanism of volcanic DLP events around the Moho (crust-mantle boundary) beneath volcanoes. One reasonable mechanism capable of producing their initial fractures is the effect of thermal stresses. Since ascending magma diapirs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 30 publications
0
40
0
1
Order By: Relevance
“…6). DLP events are commonly observed in volcanically active regions, including beneath many of the volcanoes in the Cascade Range34, and these events are thought to be caused by the movement or cooling of magmatic fluids3536. The DLP at Mount St Helens are located near the edge of the low velocity column observed in the iMUSH tomography (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…6). DLP events are commonly observed in volcanically active regions, including beneath many of the volcanoes in the Cascade Range34, and these events are thought to be caused by the movement or cooling of magmatic fluids3536. The DLP at Mount St Helens are located near the edge of the low velocity column observed in the iMUSH tomography (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, if we consider deep volcanic LFEs in central Hokkaido identified by JMA (i.e., orange circles in Figure ) as one type of tectonic tremor [ Aso et al , , ; Aso and Ide , ], observations by JMA confirm our assumption that ambient tremor occurs in this region. However, the differences between tectonic LFEs in the Nankai tremor zone and deep volcanic LFEs in central Hokkaido have not been thoroughly studied [ Obara , ; Aso and Tsai , ]. In contrast, in southeastern Kyushu, regardless of whether the triggered tremor source is correlated with the offshore shallow VLF earthquake [ Obara and Ito , ; Ito et al , ] and shallow tremor [ Obana and Kodaira , ; Suzuki and Yamashita , ] or the inland tectonic tremor [ Idehara et al , ], our observations have further confirmed that triggered tremor could be a useful tool for inferring background tremor.…”
Section: Discussionmentioning
confidence: 99%
“…With presence of magma/fluid and their movement, the physical mechanisms of these DLPs might be shear faulting, since high fluid pressure due to compressive tidal stress would reduce effective normal stress on faults, which would weaken the strength of the fault or fault network. The presence of magma/fluid does not necessarily rule out the magma cooling model (Aso & Tsai, ), considering possible existence of fluid during long‐term cooling process of the magma.…”
Section: Tidal Modulation Of Dlpsmentioning
confidence: 99%
“…Understanding the physical mechanism of DLPs could provide insights on (1) the magma/fluid migration process (e.g., Shapiro et al, ), (2) forearc mantle wedge dynamics (Vidale et al, ), and (3) volcanic eruption forecasting (e.g., Chouet, ). Based on observations, several hypotheses have been proposed to interpret the source process of DLPs, including dehydration embrittlement of already‐serpentinized mantle material (e.g., forearc DLPs in western Oregon by Vidale et al, ), magma and/or fluid movement (e.g., Shapiro et al, ; Ukawa & Ohtake, ), thermal strain from magma cooling (Aso & Tsai, ), as well as others (e.g., Aki & Koyanagi, ; Chouet, ).…”
Section: Introductionmentioning
confidence: 99%